Nuclear forensic analysis of thorium materials: recreation of a legacy processing method - Holland, Erin; Higginson, Matthew A.; Kaye, Philip; Scott, Thomas B.; Martin, Tomas; Gilligan, Christopher R. D.; Kennedy, Karen; Cross, Samuel; Brook, Christopher (Frontiers in Nuclear Engineering, 2025)
Nuclear forensic science aims to correlate measurable parameters to the processing history of nuclear materials to support law enforcement investigations. Controlled studies on elemental fractionation with processing are valued on materials of known provenance to validate methods and signatures. There is need to understand how useful current applied techniques are when applied to thorium materials. In this study, we discuss the potential nuclear forensic signatures in thorium materials and report an academic study processing a monazite ore of known provenance through a historic industrial process to thorium dioxide. The measurements traced a variety of ‘fingerprint’ material properties and impurities through the processing route. It was shown that radiometric methods, relative rare earth element abundances, impurities, radiochronometry and microscopy were useful for characterising the material.